An Adaptive Droop Control for Power Sharing Between Three Phase Parallel Inverter in Autonomous Microgrid - Parajuli, Ananta; Bista, Krishna; KC, Krishna; Bhandari, Binod (KEC Journal of Science and Engineering, 2024)
The development of an adaptive droop controller is for power sharing between three-phase parallel inverters. Traditionally, droop controllers have been employed in conventional power systems to allocate the load among generators with varying capacities. Our approach involves the utilization of an adaptive control technique. This method is designed for a setup involving three-phase parallel inverters linked to an AC microgrid, to enhance the proportional distribution of active power despite changes in feeder network characteristics and loads. The proposed control mechanism automatically tunes the frequency droop parameter to address mismatch frequencies. The system includes two sets of three-phase inverters regulated by a combination of P-F droop control, an enhanced droop control loop, and PI controllers. The adaptive droop coefficient control is capable of addressing problems where power distribution inaccuracies arise due to different line loads as well as different inverter capacities.